PENGARUH BIMBINGAN KELOMPOK TERHADAP PENURUNAN MASALAH DIBIDANG PENDIDIKAN DAN PEMBELAJARAN (PDP) SISWA KELAS VIII MTS DARUL HIKMAH PEKANBARU TAHUN AJARAN 2015/ 2016 - Mhd Muhdori; Tri Umari; Rosmawati Rosmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aimed to determine the effect of group guidance to degradation problems in the fields of education and learning (PDP), a student of class VIII MTs Darul wisdom pekanbaru the academic year 2015 / 2016. The research was conducted in MTs Darul Hikmah Pekanbaru from March 2016 to May 2016. Methods this is a quasi-experimental study. Forms of this design is the development of a true experimental desing is difficult to carry out. This research is true experimental design. True experimental design research that there are two groups of experimental and control groups. Research subjects in this study were students of class VIII MTs Darul Hikmah Pekanbaru who have a problem of education and learning. Data collection instrument used was the General AUM. Data analysis technique used is the technique of nonparametric statistical correlation Wilcoxon test and Spearman Rank Test. Based on the results of Wilcoxon test is apparently a difference of education and learning problems of students before and after the implementation of group counseling. Of Spearman Rank test conducted at the conclusion could influence group counseling services to the students' social intelligence that is equal to 16%, while 84% are influenced by other factors originating from within or from the student environment.Keywords: Guidance Group, Problems, Education, Learning